The Information System for Visiting Prisoners in Prisons Class IIA of Bengkulu - Vike Sonytro (Jurnal Komputer, Informasi dan Teknologi, 2021)
Information Systems are important because they produce information and help make decisions so that their intelligence and abilities can be the same as humans. the writer wants to design an Information System in the Correctional Institution which is a coaching institution for prisoners but the system used is still a Manual, especially for visiting Section where this system still has many obstacles, so the writer wants to research and assist officers by making a JAVA application about the information system for visiting prisoner in Prison class IIA of Bengkulu which aims to save time and find out information from guest visits to prisoners so that they consider to data collection. This information system is designed using a JAVA application with MySQL database in XAMPP, the application program used is Net Beans which is a container in making various programs where net beans IDE is also Open Source and this system uses a method that describes what data the existence and explanation of a picture or incident regarding guest visits to prisoners in Prison Class IIA of Bengkulu. The result of this research is an integrated information system with Prison Class IIA of Bengkulu, involving the Admin and Employees to input the data that has been obtained which will be processed by the system and produce a Prisoner Data Report and Guest Data Report.